Augmented Surgical Treatment in Patient with Partially Accomodative Esotropia: Poster Presentation - Case Report - Resident - PRADISTYA SYIFA YUDIASARI; Feti Karfiati; Mayasari Wahyu Kuntorini; Irawati Irfani; Primawita Oktarima; Sesu Caesarya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Esotropia is a disorder of the position of the eyeball when the eye deviates inward. Surgical treatment is indicated when the eyes are not aligned with the glasses. We report a case of augmented surgical treatment in a partially accommodative esotropia patient. Case Illustration : A 18-year-old girl comes to the hospital with vision loss in both eyes since 1 year prior admission. Ocular alignment sinne correction was 300 (Figure 1) and cum correction was 150. Prism alternate cover test (PACT) showed deviation in sinne correction distance 60?BO dan near 50?BO, and deviation in cum correction distance 40?BO dan near 35?BO. Surgical formula with augmented surgery was (60?BO + 40?BO)/2 equal to 50?BO. Patient was diagnosed with Compositus Hypermetropia ODS + Partially Accommodative Esotropia. Patient underwent bilateral medial rectus recess surgery of 6 mm. Ophthalmology examination after 1 and 2.5 month surgery showed ocular alignment without spectacles showed microtropia and with spectacles showed orthotropia (Figure 2, 3a and 3b). Discussion : Various approaches can improve outcomes, including using different surgical formulas. Augmented surgery are the mean of deviation with and without surgery as the final deviation surgical formula. Conclusion : The amount of surgery in strabismus was based on the size of preoperative deviation. Augmented surgical treatment can be one of the choices to determine preoperative deviation in an esotropia patient.